“The world is in a new phase of multipolar competition with strong overtones from the U.S.-China bilateral rivalry” - CEBRI-Journal, (CEBRI-Revista: Brazilian Journal of International Affairs, 2022)
Félix E. Martín conversou com os editores da CEBRI-Revista.